2018
DOI: 10.3889/oamjms.2018.156
|View full text |Cite
|
Sign up to set email alerts
|

Is the rs1801282 (G/C) Polymorphism of PPAR - Gamma Gene Associated with T2DM in Iraqi People?

Abstract: BACKGROUND:Pro12Ala (rs1801282) is a common polymorphism of the human PPAR-γ gene. Studies have demonstrated conflicting results about its association with T2DM worldwide. There are no reports about such possible association among Iraqi people.OBJECTIVES:This study aims at finding out whether having the mutant allele (Ala12) might be associated with T2DM among Iraqi people.METHODS:One hundred and ninety-two Arabic Iraqi adult subjects (97 with T2DM and 95 controls) were genotyped using PCR- RFLP. Clinical, ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
0
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 60 publications
1
0
0
2
Order By: Relevance
“…The frequencies of the PPARγ Pro12Ala genotypes were 91.9% for C/C, 8.1% for C/G and 0% for G/G in the Emirati population [39], compared to 87.3%, 11.6%, and 1.1%, respectively, in the diabetic group data in the present study. Similar to our findings here, recent studies in Iraqi and Egyptian populations reported no significant association in their cohorts with T2DM [40,41]. In addition, the Egyptian study showed no significant differences in PPARγ Pro12Ala genotypes and T2DM parameters (BMI, HbA1c, FBS, triglyceride, and cholesterol) [40].…”
Section: Discussionsupporting
confidence: 88%
“…The frequencies of the PPARγ Pro12Ala genotypes were 91.9% for C/C, 8.1% for C/G and 0% for G/G in the Emirati population [39], compared to 87.3%, 11.6%, and 1.1%, respectively, in the diabetic group data in the present study. Similar to our findings here, recent studies in Iraqi and Egyptian populations reported no significant association in their cohorts with T2DM [40,41]. In addition, the Egyptian study showed no significant differences in PPARγ Pro12Ala genotypes and T2DM parameters (BMI, HbA1c, FBS, triglyceride, and cholesterol) [40].…”
Section: Discussionsupporting
confidence: 88%
“…Некоторые исследования, проведенные на различных популяциях, ассоциации генотипа GG полиморфизма rs1801282 гена PPARG с риском развития СД 2 не показали [32][33][34][35][36][37][38][39][40]. Однако при оценке влияния сочетания ряда полиморфизмов генов оказалось, что, например, генотип СС гена rs1801282 PPARG повышает риск СД 2 при наличии генотипа АТ полиморфизма rs9939609 гена FTO [41].…”
Section: Reviewunclassified
“…2007 ve 2008 yıllarında gerçekleştirilen GWA çalışmalarında da T2D ile ilişkisi teyit edilen birkaç genden biri de yine PPARG geni (P12A varyantı)'dir [20][21][22]. PPARG'nın Tip 2 diyabet ile ilişkisine yönelik daha önceleri de çalışmalar yapılmış ancak hastalık bakımından koruyucu [14,[23][24][25][26], risk faktörü [27][28][29][30] ya da herhangi bir ilişkisinin olmadığı [31][32][33][34][35] gibi farklı populasyonlarda farklı sonuçlar rapor edilmiştir. Bizim çalışmamızda, Tip 2 diyabet ile PPARG genindeki Pro12Ala polimorfizmi arasında herhangi bir ilişki tespit edilmemiştir.…”
Section: Pro12ala'nın T2d Ve Fentotipler Ile Ilişkisiunclassified